​Individual determinants of norms of justice: the particular case of far-right supporters.​ - Ramos, A.; Correia, I.; Vala, J.; Santana Pereira, J. (European societies in times of turmoil Snapshots from the European Social Survey, 2022)
Following the understanding of Koller (1995) justice refers to the normative conception of the allocation and distribution of resources and burdens in a social aggregate. Four main norms on how to proceed with this distribution have been proposed: meritocracy (Kluegel and Smith, 1986) or equity (Adams, 1963); equality and need (Deutsch, 1975); and entitlement (Miller, 1979). The aim of this presentation is to analyse the individual determinants of each of the four justice norms in European countries, with a special focus on the ideological cleavage between far- left and far- right political orientations. Differences and similarities between extreme left and extreme right have been deeply studied. While some authors have pointed similarities, for instance, authoritarian personality (e.g. Shills 1954), far- right and far- left supporters hold sharply contrasting views, among many others, on questions of social welfare, economic equality, racial equality, women's rights or sexual freedom (McClosky and Chong, 2009), as well as on the political realm, namely in the extent to which they embrace populist attitudes (Marcos-Marne et al., 2021). How different are far -left and far- right supporters regarding social justice norms? Moreover, in what degree are far- right supporters distinct not only from the far- left, but also from the center right allies.? Results drawn on data from the ESS9 module on Justice and Fairness in Europe, show that far- right supporters are not only significantly different from the far- left, as from the rest of the political orientations along the political spectrum. In fact, far- right supporters display a higher support to the norms of meritocracy and entitlement, and a lower support to the norms of need and equality than the remainder respondents. Importantly, these effects remain in the presence of traditional control variables, including the belief in a just world.